Wild in the U.S.A. - Hammerslough, Jane.; Corwin, Jeff.; Animal Planet (Television network) (New York : Scholastic, 2003)
Animal Planet star Jeff Corwin travels to Alaska, Florida, Arizona, and Louisiana to profile such unique U.S. animals as armadillos, Steller sea lions, desert bats, and alligators.
"Based on the Animal Planet program The Jeff Corwin Experience."
1110L
Keywords: Animals -- Juvenile literature; Natural history -- United States -- Juvenile literature; Animals; Natural history